2019
DOI: 10.1002/acr2.11073
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Predicts an Alternate Immune System Phenotype in Systemic Lupus Erythematosus

Abstract: ObjectiveType I interferon (IFN) is important to systemic lupus erythematosus (SLE) pathogenesis, but it is not clear how chronic elevations in IFN alter immune function. We compared cytokine responses after whole blood stimulation with Toll‐like receptor (TLR) agonists in high‐ and low‐IFN SLE patient subgroups.MethodsSLE patients and nonautoimmune controls were recruited, and SLE patients were categorized as either high or low IFN. Whole blood was dispensed into tubes coated with lipopolysaccharide (LPS), ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 29–38 In two studies concurrent validity was tested between the IFN-inducible protein and two other techniques (flow cytometry for SIGLEC-1 22 39 as well as IFN-α protein 21 26 ; and gene expression as well as a reporter cell assay). 30 40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 29–38 In two studies concurrent validity was tested between the IFN-inducible protein and two other techniques (flow cytometry for SIGLEC-1 22 39 as well as IFN-α protein 21 26 ; and gene expression as well as a reporter cell assay). 30 40 …”
Section: Resultsmentioning
confidence: 99%
“…Bauer et al 29 selected IFN chemokines whose transcripts were induced by IFN-α in a microarray study but did not check whether other IFNs or inflammatory mediators also induced these proteins. Thanarajasingam et al 30 evaluated stimulation of whole blood including IFN-α, oligonucleotides with cytosine‐guanine repeats, Resiquimod (R848), LPS, IFN‐α+LPS and null (no stimulant) then measured cytokines/chemokines and IFN-α. Most of the other studies cite the evidence from Bauer et al 29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In autoimmune diseases such as SLE, pSS, and SSc, both the numbers and function, including cytokine production, of circulating pDCs are reduced. [46][47][48] In fact, a previous study showed that pDCs from patients with SLE and at-risk patients (ie, those with some features of autoimmunity but without a disease diagnosis) exhibit a senescent phenotype. 46 However, it is possible that the population of circulating pDCs is not representative of the tissue infiltrating pDC, which could still have significant pathogenic roles in autoimmunity both dependent and independent of excessive IFN-α production by these cells.…”
Section: Ifn-i In Autoimmunitymentioning
confidence: 99%